Technology-Based Tourism Strengthening Strategies In Empowering Community Agro-Tourism Blimbing Gardens In Ngringinrejo Kalitidu Village - Musta’ana, Musta’ana; Suhindarno, Heny (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to identify strategies for strengthening tourism through community empowerment in the use of technology in Agrotourism Belimbing Garden in Ngringinrejo Village, Kalitidu, Bojonegoro. The focus of this research is on the importance of innovation and community involvement in an effort to increase the number of tourists as well as the contribution of the local economy. The research used a descriptive method with a qualitative approach, involving field observations, semi-structured interviews with stakeholders, and documentation. Informants consisted of the head of the BUMDes, the head of the tourism awareness group, as well as the local community. The results showed that the management of Belimbing Agrotourism has not fully utilized technology due to limited human resources (HR) who are competent in the field of technology. In addition, the COVID-19 pandemic has caused a decrease in the number of tourists which has an impact on the local economy. Therefore, efforts are needed to increase the capacity of human resources, especially in the field of technology, as well as more modern promotional strategies to increase tourist attractiveness. The implication of this research is the need to increase HR competencies and implement more effective technology-based promotional strategies to restore and develop local tourism potential in a sustainable manner